Addressing Learning Loss in Mathematics: A Research-Based Intervention - Campit, Marvin Nonoy B.; Enomis, Cristine A.; Castillo, Desiree T.; Tuan, Jane C. (Jurnal Pendidikan Indonesia Gemilang, 2024)
This study aimed to investigate the "learning loss" resulting from recent academic disruptions. This study used a classroom action research, utilizing peer tutoring as the primary intervention amidst various psychological factors. The pretest identifies ten least-mastered mathematics skills, including simplifying numerical expressions, operations on integers, converting fractions to decimals, ordering rational numbers, and solving word problems. Challenges are also noted in approximating volume and area, understanding angles, and interpreting graphical data. Focus group discussions highlight the positive feedback for the intervention and factors contributing to learning loss, such as limited study time, connectivity issues, social media distractions, poor study habits, and math difficulties. Implementing tutorial intervention before the post-test effectively addresses learning loss and significantly reduces learning gaps.